Comparative scheme of the thought of Eugenio Raúl Zaffaroni and Carlos Santiago Nino in relation to the theory of penalty: Navigation notebook - Alegría Hidalgo, Juan (2008)
The theory of the sanction, its purposes and the general object of the criminal legal system, have always brought substantial questioning by the dogmatic penitentiary, that is why its legitimacy has been questioned, for the lack of better arguments. It is in this background that the teacher Eugene Raul Zaffaroni from Argentina, sets out certain positions by which he questions the entire Latin American criminal system. In this context, began the debate with criminal attorney and well known philosopher of law Carlos Santiago Nino. It seems to us very interesting to know the points of divergence as well as the conformities between both. That is the reason for the present work, which is presented as guide for further discutions and developments.